2017
DOI: 10.1101/140764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct core promoter codes drive transcription initiation at key developmental transitions in a marine chordate

Abstract: Development is largely driven by transitions between transcriptional programs. The initiation of transcription at appropriate sites in the genome is a key component of this and yet few rules governing selection are known. Here, we used cap analysis of gene expression (CAGE) to generate bp-resolution maps of transcription start sites (TSSs) across the genome of Oikopleura dioica, a member of the closest living relatives to vertebrates. Our TSS maps revealed promoter features in common with vertebrates, as well … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This may be achieved through the use of alternative start sites that either include or exclude the trans-splice site. Supporting this, a male-specific promoter motif recently identified in O. dioica (Danks et al, 2018) causes the exclusion of trans-splice sites, and consequently the lack of a spliced leader on resulting transcripts, in many cases. Given the strong association of trans-splicing with maternal mRNA, mTOR regulation via the spliced leader is likely an underlying mechanism for the adjustment of egg numbers according to nutrient levels in O. dioica (Troedsson et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…This may be achieved through the use of alternative start sites that either include or exclude the trans-splice site. Supporting this, a male-specific promoter motif recently identified in O. dioica (Danks et al, 2018) causes the exclusion of trans-splice sites, and consequently the lack of a spliced leader on resulting transcripts, in many cases. Given the strong association of trans-splicing with maternal mRNA, mTOR regulation via the spliced leader is likely an underlying mechanism for the adjustment of egg numbers according to nutrient levels in O. dioica (Troedsson et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…The majority of our weakly-translated, Torin 1-resistant, trans-spliced transcripts therefore likely represent dormant maternal mRNAs stocked in oocytes. We used both tiling microarray (Danks et al, 2013) and cap analysis of gene expression (CAGE) (Danks, Navratilova, Lenhard, & Thompson, 2018) data from O. dioica oocytes to determine the set of oocyte-stocked mRNAs. As expected, we found that the translational efficiency of oocyte transcripts in control animals was significantly lower than that of non-oocyte transcripts (mean oocyte log 2 (TE) = -0.80; mean non-oocyte log 2 (TE) = 0.45; Welch two-sample t-test: t = -57.494, df = 14002, P-value < 2.2 x 10 -16 ) ( Figure 3D, Figure S4), and the effect of Torin 1 was significantly reduced (mean oocyte log 2 (Δ) = -0.17; mean non-oocyte log 2 (Δ) = -0.97; Welch two-sample t-test: t = 43.54, df = 12832, P-value < 2.2 x 10 -16 ) ( Figure 3E).…”
Section: Trans-spliced Transcripts Dominate the Primary Translationalmentioning
confidence: 99%
See 3 more Smart Citations